A review of different decision-making models for fruit farmers - Mohayidin, Mohd Ghazali (Malaysian Agricultural Economics Association, 1984)
Farmers' decisions are inoariably taken .under the conditions of uncertainty. The purpose of this paper is to review the expected accounting profit model and to compare how well it explains farmers' decision on cropping-pattern selection with two other models, the negative exponential utility and the market-based profit models. The expected accounting profit model isfound to perform better than the other two models in explainingfanners' choice.